2020
DOI: 10.1111/pace.13914
|View full text |Cite
|
Sign up to set email alerts
|

Is left bundle branch block pattern on the ECG caused by variable ventricular activation sequence?

Abstract: Background:The presence and extent of ventricular dyssynchrony are currently assessed from the QRS complex morphology and width. However, similar electrocardiography (ECG) pattern may be caused by variable ventricular activation sequence. This may then contribute to interindividually different response to cardiac resynchronization therapy (CRT).Methods: Electroanatomical mapping and magnetic resonance imaging scan were performed in 11 patients with left bundle branch block (LBBB, QRS 170 ± 14 ms) and heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Instead, the LV was consistently activated through transmyocardial conduction. 18 Our mapping study does not support the hypothesis of residual anterograde Purkinje conduction as the etiology for LAD in patients with LBBB. In patients with NA, activation during spontaneous rhythm and during RVAP differed in terms of pattern but not duration.…”
Section: Mechanisms Of Lad In Lbbbcontrasting
confidence: 90%
“…Instead, the LV was consistently activated through transmyocardial conduction. 18 Our mapping study does not support the hypothesis of residual anterograde Purkinje conduction as the etiology for LAD in patients with LBBB. In patients with NA, activation during spontaneous rhythm and during RVAP differed in terms of pattern but not duration.…”
Section: Mechanisms Of Lad In Lbbbcontrasting
confidence: 90%
“…Even though scar burden and distribution can be determined more accurately using imaging modalities such as cardiac magnetic resonance late gadolinium enhancement (CMR‐LGE) or SPECT MPI, 17,18 the standard 12‐lead ECG, as a screening tool, is widely applied with the advantage of being easily available. Strauss et al showed that chronic myocardial scars could be quantified using the ECG despite the presence of LBBB 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The amplification of repolarization gradients between segments of the left ventricle is the electrophysiological basis for T-wave memory. The LV was activated only through transmyocardial conduction starting after the RV activation onset, and then the activation spread centrifugally over the anterior and inferior wall in patients with LBBB-like patterns [19]. The maximum repolarization gradients in patients with CLBBB are the anterior and inferior walls.…”
Section: Twis In Different Leadsmentioning
confidence: 99%